Estrategias de marketing en innova centro Cerámico Babahoyo 2 de la ciudad de Babahoyo, periodo 2022. - Palacios Vargas, Dayana Yamilet (2023)
The research was carried out at INNOVA Centro Ceramico Babahoyo 2, a private company specialized in the sale of construction finishes, which includes a variety of products such as ceramics, porcelain tiles, faucets, sinks, toilets and granite slabs. These finishes are essential elements that are applied to a structure or building once the main construction phase has been completed. The main objective of the research was to identify the marketing strategies that are being implemented at INNOVA Centro Ceramico Babahoyo 2 in the city of Babahoyo. The research is part of the research line: Administrative Financial Management, Tax, Audit and Control, with the Marketing and Commercialization subline. This study is linked to a project of internships and pre-professional practices related to the Management of Managerial and Administrative Processes in the public and private sectors, supervised by a teacher. The methodology used in the research is descriptive, with a qualitative approach. The interview technique was used with a structured questionnaire to obtain specific information on the product, price, promotion and distribution variables. The research results revealed that the company has implemented a strategic marketing mix that contributes to its sustainability, especially in a highly competitive market. The importance of the company director's strategic decisions in his ability to compete effectively in this environment was highlighted.